Evaluation of motion mitigation using abdominal compression in the clinical implementation of pencil beam scanning proton therapy of liver tumors. Issue 2 (30th January 2017) - Lin, Liyong; Souris, Kevin; Kang, Minglei; Glick, Adam; Lin, Haibo; Huang, Sheng; Stützer, Kristin; Janssens, Guillaume; Sterpin, Edmond; Lee, John A.; Solberg, Timothy D.; McDonough, James E.; et al.
Abstract : Purpose: To determine whether individual liver tumor patients can be safely treated with pencil beam scanning proton therapy. This study reports a planning preparation workflow that can be used for beam angle selection and the evaluation of the efficacy of abdominal compression (AC) to mitigate motion. Methods: Four‐dimensional computed tomography scans (4DCT) with and without AC were available from 10 liver tumor patients with fluoroscopy‐proven motion reduction by AC, previously treated using photons. For each scan, the motion amplitudes and the motion‐induced variation of water‐equivalent thickness (ΔWET) in each voxel of the target volume were evaluated during treatment plan preparation. Optimal proton beam angles were selected after volume analysis of the respective beam‐specific planning target volume (BSPTV). M⊥80 and ΔWET80 derived from the 80th percentiles of perpendicular motion amplitude (M⊥ ) and ΔWET were compared with and without AC. Proton plans were created on the average CT to achieve target coverage similar to that of the conventional photon treatments. 4D dynamic dose calculation was performed postplan by synchronizing proton beam delivery timing patterns to the 4DCT phases to assess interplay and fractionation effects, and to determine motion criteria for subsequent patient treatment. Results: Selected coplanar beam angles ranged between 180° and 39°, primarily from right lateral (oblique) and posterior (oblique) directions. While AC produced a significant reduction in mean Liver‐GTV dose, any reduction in mean heart dose was patient dependent and not significant. Similarly, AC resulted in reductions in M⊥, ΔWET, and BSPTV volumes and improved dose degradation (ΔD95 and ΔD1 ) within the CTV. For small motion (M⊥80 < 7 mm and ΔWET80 < 5 mm), motion mitigation was not needed. For moderate motion (M⊥80 7–10 mm or ΔWET80 5–7 mm), AC produced a modest improvement. For large motion (M⊥80 > 10 mm or ΔWET80 > 7 mm), AC and/or some other form of mitigation strategies were required. Conclusion: A workflow for screening patients' motion characteristics and optimizing beam angle selection was established for the pencil beam scanning proton therapy treatment of liver tumors. Abdominal compression was found to be useful at mitigation of moderate and large motion.